The Influence of Principal Leadership and Teacher Collaboration on Public Elementary School Teachers’ Performance - Noviliana Noviliana; Syaiful Eddy; Dessy Wardiah (Journal of Social Work and Science Education, 2027)
This study aims to determine and describe the influence of principal leadership and teacher collaboration on the performance of public elementary school teachers in Cluster 2, Tanjung Lubuk District, encompassing six schools. A quantitative descriptive method was employed. The population comprised 129 teachers, with a sample of 97 respondents determined through appropriate sampling techniques. Data were collected using questionnaires, observation, and documentation. Analyses included normality, linearity, multicollinearity tests, simple and multiple correlation, simple regression, t-tests, and F-tests. The findings reveal that principal leadership and teacher collaboration significantly influence teacher performance. The more professional teachers are in executing their duties and the higher the value of collaboration, the better their performance. The ANOVA test confirmed significance with F-count > F-table, leading to rejection of H₀. This study provides empirical evidence from a clustered rural school setting in Tanjung Lubuk District, demonstrating the combined predictive power of leadership and collaboration on teacher performance in an under-researched multi-school context. Findings underscore the need for school principals to simultaneously strengthen leadership capacity and foster collaborative teacher cultures to optimize performance outcomes. This research contributes actionable insights for educational policymakers and administrators, affirming that teacher performance is substantially enhanced when authoritative leadership is complemented by structured teacher collaboration, offering a foundational reference for performance improvement strategies in similar rural elementary school clusters.